Transformation of Islamic Education Management in the Digital Age: A Social Study at SMP Nurul Ulama Tenggarang Bondowoso - Dausat, Muhammad Jangki; Al Rosid, Moh. Harun (Universitas Islam Negeri Mahmud Yunus Batusangkar, 2025)
Digital transformation has brought significant changes in education management, including in Islamic education institutions. Education management that was previously conventional is now experiencing a paradigm shift towards digitalization that emphasizes efficiency, transparency, and accountability. This research aims to analyze the form of transformation of Islamic education management in the digital era, focusing on a case study at SMP Nurul Ulama Tenggarang Bondowoso, a secondary level Islamic education institution that has begun to integrate technology in its managerial and academic systems. This research uses a descriptive qualitative approach with a case study method. Data collection techniques were conducted through in-depth interviews, participatory observation, and documentation of digital-based managerial practices. Data were analyzed through reduction, presentation, and conclusion drawing. The results show that the management transformation in this school includes the digitalization of administration, the use of online learning platforms, increasing teachers' competence in technology, and strengthening spiritual values in the digital learning process. This transformation is proven to increase the efficiency of management work and the participation of teachers and students in the digital ecosystem, without neglecting the essence of Islamic values which is the spirit of Islamic education. This study suggests that digital transformation be carried out as a whole, with the support of internal regulations, human resource training, and infrastructure strengthening to ensure the sustainability and quality of Islamic education in the digital era.